Ilex decidua 'Byers Golden' Golden Possumhaw: FPS-269/FP269, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides a detailed overview of the Ilex decidua ‘Byers Golden’, commonly known as Golden Possumhaw. It describes the plant’s characteristics, including its height, spread, leaf arrangement, and fruiting habits. The document highlights its uses in landscaping, such as in buffer strips, parking lot islands, and residential street trees. It also discusses the plant’s growth requirements, including light, soil, and water needs, and mentions its moderate drought tolerance and pest resistance. Additionally, the document notes the plant’s ornamental features, such as its persistent fruits and winter interest. Original publication date October 1999.